Applying complexity science to air traffic management. (January 2015) - Cook, Andrew; Blom, Henk A.P.; Lillo, Fabrizio; Mantegna, Rosario Nunzio; Miccichè, Salvatore; Rivas, Damián; Vázquez, Rafael; Zanin, Massimiliano
Abstract: Complexity science is the multidisciplinary study of complex systems. Its marked network orientation lends itself well to transport contexts. Key features of complexity science are introduced and defined, with a specific focus on the application to air traffic management. An overview of complex network theory is presented, with examples of its corresponding metrics and multiple scales. Complexity science is starting to make important contributions to performance assessment and system design: selected, applied air traffic management case studies are explored. The important contexts of uncertainty, resilience and emergent behaviour are discussed, with future research priorities summarised. Highlights: Complexity science techniques make valuable contributions to air transport management. Complex network theory offers metrics and methods for studying air transport networks. Performance changes in important ways under various flight prioritisation rules. Community detection methods have an important role to play in air transport planning. Future research avenues for resilience, emergence and complex metrics are discussed.